Modeling thoracic aortic genetic variants in the zebrafish: useful for predicting clinical pathogenicity? - Prendergast, Andrew; Sheppard, Mary B.; Famulski, Jakub K.; Nicoli, Stefania; Mukherjee, Sandip; Sips, Patrick; Elefteriades, John A. (Frontiers in Cardiovascular Medicine, 2025)
Thoracic aortic aneurysm and dissection (TAAD) significantly impact cardiovascular morbidity and mortality. A large subset of TAAD cases, particularly those with an earlier onset, is linked to heritable genetic defects. Despite progress in characterizing genes associated with both syndromic and non-syndromic heritable TAAD, the causative gene remains unknown in most cases. Another important bottleneck in the correct and timely diagnosis of TAAD is the large proportion of variants of unknown significance (VUS) that are routinely encountered upon medical genetic testing. Reliable functional modeling data is required to accurately identify new causal genes and to determine the pathogenicity of VUS. To address this gap, our collaborative effort—comprising teams from Yale University, University of Kentucky, and Ghent University—explores a novel approach: modeling TAAD in zebrafish. Leveraging the unique advantages of this animal model promises to allow for accelerated variant pathogenicity assessment, ultimately enhancing patient care. In this review, we critically explore the currently available zebrafish-based approaches that can be used for testing pathogenicity of genes and variants related to TAAD, and we offer an outlook on the implementation of these strategies for clinical applications.